2022
DOI: 10.1002/pbc.29860
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prognostic value of central nervous system involvement in infants with B‐cell precursor acute lymphoblastic leukemia treated according to the MLL‐Baby protocol

Abstract: Aim:The aim of the study was to evaluate the incidence and prognostic impact of central nervous system (CNS) involvement in infants with B-cell precursor acute lymphoblastic leukemia (BCP-ALL), as well as its relation with minimal residual disease (MRD) data.Methods: A total of 139 consecutive infants with BCP-ALL from the MLL-Baby trial were studied. Cerebrospinal fluid (CSF) samples were investigated by microscopy of cytospin slides. MRD was evaluated according to the protocol schedule by flow cytometry and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…In the group of 50 infants with CNS involvement, as many as 28 had a recurrence (EFS = 0.27, cumulative incidence of relapse (CIR) = 0.65), while among 89 CNS patients—negative—21 experienced a relapse (EFS = 0.58, CIR = 0.26, p < 0.001) for both. In total, 11 of the 49 patients with registered relapses had CNS infiltration (five isolated CNS relapses and six combined CNS and BM relapses) [ 76 ]. CNS involvement is more frequently observed in infants than in older children with KMT2A -r and is associated with a worse prognosis.…”
Section: Clinical Outcome and Interfant Protocolmentioning
confidence: 99%
“…In the group of 50 infants with CNS involvement, as many as 28 had a recurrence (EFS = 0.27, cumulative incidence of relapse (CIR) = 0.65), while among 89 CNS patients—negative—21 experienced a relapse (EFS = 0.58, CIR = 0.26, p < 0.001) for both. In total, 11 of the 49 patients with registered relapses had CNS infiltration (five isolated CNS relapses and six combined CNS and BM relapses) [ 76 ]. CNS involvement is more frequently observed in infants than in older children with KMT2A -r and is associated with a worse prognosis.…”
Section: Clinical Outcome and Interfant Protocolmentioning
confidence: 99%
“…[3][4][5][6] In contrast, infants with germline KMT2A (KMT2A-g), who account for nearly a quarter of all BCP-ALL patients in this age group, have a significantly better prognosis, 4,7 but still worse compared to patients with pediatric ALL (older than 1 year). Due to the rarity of KMT2A-g-ALL in infants, it is difficult to assess the value of prognostic factors known to be significant in infants with KMT2A-r 3,8 : the initial WBC count, age at diagnosis, central nervous system (CNS) involvement, 5,9 leukemia cell immunophenotype, 10,11 and parameters of therapy response, 12,13 including elimination of minimal residual disease (MRD). [14][15][16] In addition, recent studies have demonstrated the potential importance of newly identified genetic traits, including NUTM1 and PAX5 fusion genes (FG).…”
Section: Introductionmentioning
confidence: 99%